Increased urinary Smad3 is significantly correlated with glomerular hyperfiltration and a reduced glomerular filtration rate and is a new urinary biomarker for diabetic nephropathy. Issue 1 (December 2015) - Guo, Kaifeng; Lu, Junxi; Kou, Jingxin; Wu, Mian; Zhang, Lei; Yu, Haoyong; Zhang, Mingliang; Bao, Yuqian; Chen, Haibing; Jia, Weiping
Abstract Background Diabetic nephropathy is one of the major microvascular complications of diabetes. We investigated the association between urinary Smad3 (usmad3) levels, glomerular hyperfiltration, and the development of nephropathy in patients with type 2 diabetes mellitus (T2DM). Methods The usmad3 level was determined by enzyme-linked immunosorbent assay in 245 well-characterised patients with T2DM and 82 healthy control subjects. The associations of the usmad3 level with glomerular hyperfiltration, glucose and lipid profiles, and renal function were evaluated. Results The usmad3 level was significantly higher in patients with diabetes than in the control group. The level in the hyperfiltration group was higher than that in the normofiltering group, regardless of whether patients were in the normoalbuminuric or the proteinuria groups. Pearson's correlation analysis suggested that the usmad3 level was significantly correlated with age, systolic blood pressure, fasting plasma glucose, insulin, C-peptide, glycated haemoglobin, and estimated glomerular filtration rate (eGFR). A multiple linear stepwise regression analysis revealed that usmad3 levels in patients with T2DM and an eGFR ≥90 ml/min/1.73 m2 were independently and positively correlated with eGFR, whereas in patients with T2DM and eGFR <90 ml/min/1.73 m2, the levels were independently and negatively correlated with eGFR. Conclusions The usmad3 level was significantly correlated with biphasic changes in the GFR (both glomerular hyperfiltration and reduced eGFR) in patients with T2DM. Usmad3 may serve as a novel marker for hyperfiltration and for screening patients with T2DM for nephropathy.